Some characterizations of euler spirals In E3_1 - Saraçoğlu Çelik, Semra; Yaylı, Yusuf; Güler, Erhan (My University, 2016)
In this study, some characterizations of Euler spirals in E3_1 have been presented by using their main property that their curvatures are linear. Moreover, discussing some properties of Bertrand curves and helices, the relationship between these special curves in E3_1 have been investigated with different theorems and examples. The approach we used in this paper is useful in understanding the role of Euler spirals in E3_1 in differential geometry.
Keywords: Curvature; Cornu spiral; Bertrand curve pair